Indigenous peoples and the collaborative stewardship of nature - Sherman, Kathleen Pickering, speaker; Sherman Richard T., speaker; Unidentified speaker (Colorado State University. Libraries, 2011)
On the Pine Ridge Indian Reservation in South Dakota, Lakota environmental values are embodied in historical, cultural and spiritual connections with land and wildlife. These values are often lost or disregarded in Western approaches to reservation land management. The Indigenous Stewardship Model is a starting point for integrating culturally appropriate solutions to issues of natural resource stewardship and conflict resolution. Developed collaboratively by Oglala Sioux tribal member Richard Sherman and a wide array of tribal elders, indigenous non‐profit organizations, academics and natural resource agencies, the Indigenous Stewardship Model seeks to construct a common language of mutual understanding.
The Indigenous Stewardship Model: learning the language of collaboration
Presented at the Fall 2011 Center for Collaborative Conservation (https://collaborativeconservation.org/) Seminar and Discussion Series, "Collaborative Conservation in Practice: Indigenous Peoples and Conservation", October 4, 2011, Colorado State University, Fort Collins, Colorado. This series focused on Indigenous Peoples and Conservation.
Kathleen Pickering Sherman is Professor and Chair of the Department of Anthropology at Colorado State University, where she has been on the faculty since 1997. Before starting graduate school, she worked as a legal services attorney on the Pine Ridge Indian Reservation in South Dakota, and continues to conduct research there on household subsistence and community‐based economic development. Her research interests include economic anthropology, traditional ecological knowledge, tribal economic development, collaborative ecosystem conservation and natural resource management, and the impacts of globalization on indigenous communities. She completed her graduate studies at University of Wisconsin-Madison, and has a law degree from New York University School of Law.
Richard Sherman was born and raised on the Pine Ridge Indian Reservation in South Dakota and is a member of the Oglala Sioux Tribe. He has worked most of his life on all aspects of fisheries, wildlife, and buffalo management, ethnobotany, and Indigenous stewardship methods. He drafted the first comprehensive fish and wildlife code for the Oglala Sioux Tribe and created methods of inventory for wildlife conservation Reservation-wide. As Wildlife Biologist, Executive Director, and Board Member of Oglala Sioux Parks and Recreation, he actively managed the tribal buffalo herd for more than 30 years, using the values and philosophies of the Lakota people to maintain them in a wild state. He conducted several studies on the Pine Ridge Reservation focused on subsistence practices and wildlife management, including a study of the importance of home-based micro-enterprise activity for the Reservation economy and a study of small-scale native bison operators on Pine Ridge, Rosebud and Yankton. He studied wildlife management at Utah State University and has a Master's Degree in regional planning from University of Massachusetts, Amherst.
Includes recorded speech and PowerPoint presentation.
Keywords: systemic barriers; ecosystem; Indigenous Stewardship Model; scientific positivism; indigenous knowledge; ecology; epistemologcial barriers